Peran Besar Pelabuhan Tuban dalam Islamisasi Jawa - Fatkhurrozi, M. Teguh (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2023)
Every history book that discusses trade in the past, more or less the book also discusses the port in Tuban. Tuban as one of the ancient port cities in eastern Java has played an important role since centuries ago. It has been a long time since trade has taken place between the “West” and “East” world regions that have come into contact with Tuban. Merchants crossing various countries traveled very long and tiring to get commodities from distant countries. Tuban, which has always been the belle of the kingdoms in charge, was used as a trading center on the island of Java. Casparis argues that Airlangga has divided its ports or trading centers into 2, namely: Hujung Galuh port and Kambang Putih port. Hujung Galuh port is used as a local trade center because of its inland location, while Kambang Putih port is used as an international port because of its location which goes directly to the sea.